South Korea's Efforts in Indonesia Through Kimchi Gastrodiplomacy to Improve National Branding - RAFIKA, Rafika; SALAM, Syahrul (PT Keberlanjutan Strategis Indonesia, 2025)
This study will analyze South Korea's gastro-diplomacy efforts to improve national branding in Indonesia from 2015 to 2018 using the Korean Wave. This study also discusses South Korea's initiative to preserve its culture through food, including kimchi. South Korea makes these efforts to attract the global world and strives to continue to build a good image. Seeing that South Korea, with its Drama and K-pop culture, has been glanced at by international countries, South Korea is trying to market its food products. This study aims to analyze the gastro-diplomacy efforts carried out by South Korea to further promote South Korean food culture in Indonesia by using qualitative descriptive methods. Data sources were obtained from book documents, research journals, and credible internet media as supporting primary sources related to South Korean gastro diplomacy. According to the study's final findings, using kimchi gastro diplomacy in Indonesia has increased the number of kimchi lovers, South Korean restaurants in Indonesia, and imports and exports, especially in the food industry. Because the taste of South Korean and Indonesian cuisine is similar, Indonesian people easily like South Korean cuisine. Therefore, gastro diplomacy is used by South Korea to further promote South Korean food culture, especially in the field of cuisine.